Weed Responses to Crop Residues Management in a Summer Maize Cropland in the North China Plain - Jin Zhang; Lan-Fang Wu; Bin-Bin Li (Agriculture, 2021)
Crop residues management has great effects on weeds in croplands. To understand the weed responses to crop residues management and weeds impact on crop yield, a field trial with three crop residues management strategies has been conducted in the North China Plain since 2008. Weed community composition and structure across the species, morphological types, life forms, and community levels were investigated during 2019–2020. The results show that the field with crop residues retention significantly decreased weed density than that in the field with no crop residues retention. Furthermore, total crop residues retention significantly decreased weed density than half crop residues retention. Compared with no crop residues retention, the weed aboveground dry matter in the field with total and half crop residues retention significantly decreased. Meanwhile, the maize grain yield significantly increased, resulting from weeds decreased with crop residues retention on the field. Negative correlations were found between maize grain yield and the density and aboveground dry matter of monocotyledonous weeds. These findings indicate that long term crop residues retention under conventional tillage might be an effective agronomic practice to retard weed growth. However, the mechanism of crop residues retention on weed control is still needed to research.